Determinant of Stock Investment Intention on Young Generation in Indonesia - Hakim, Lukman; Navilla, Meda Shava; Haque, Farhat (Economics Department, Faculty of Economic and Islamic Business, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
The young generation is a generation that has a major contribution to development in Indonesia. Malang City was chosen as the object of this research because the level of financial literacy and inclusion in Malang City has high rates. This study aims to determine whether financial literacy and inclusion affect the investment intention of young generation stocks in Malang City. This study used primary data with descriptive quantitative methods and analyzed using multiple linear regression analysis. The results of this study indicate that financial literacy and inclusion have a positive and significant effect on stock investment intentions of the young generation in Malang City. This research is expected to contribute to improving investment policy, especially stock investment in Malang City. So that stock investment in Malang City can have a positive influence on increasing the income of the people of Malang City in a sustainable manner.